PART A
Convert both of them into Standard Form.
3x = 3y - 3
Subtract 3y from both sides.
3x - 3y = -3
y = x + 1
Subtract x from both sides.
-x + y = 1
Multiply everything by -1 to make x positive.
x - y = -1
3x - 3y = -3
x - y = -1
Multiply x - y = -1 by -3 to make -y the opposite of -3y in 3x - 3y = -3.
3x - 3y = -3
-3x + 3y = 3
Add the equations together.
3x - 3y = -3
-3x + 3y = 3
equals
0 = 0
There are infinitely many solutions.
PART B
First of all, I didn't use graphing because I'm more used to graphing in the y intercept form instead of the x intercept form. I also didn't use substitution because it would take longer than addition, the method I used. Another reason I used addition is because I could easily multiply the -y by -3 to cancel out the -3 in the other equation. When I did this, I realized not only did the y variable cancel out, but so did the x variable and the solution, making it the most efficient way to get the answer.